Post‐transplant lymphoproliferative disorder in adult liver transplant recipients: a South American multicenter experience. (13th June 2013) - Mendizabal, Manuel; Marciano, Sebastián; dos Santos Schraiber, Luciana; Zapata, Rodrigo; Quiros, Rodolfo; Zanotelli, Maria Lucia; Rivas, María Marta; Kusminsky, Gustavo; Humeres, Roberto; Alves de Mattos, Angelo; Gadano, Adrián; Silva, Marcelo O.
Abstract Post‐transplant lymphoproliferative disorder (PTLD) is a major and potentially life‐threatening complication after solid‐organ transplantation. The aim of this study was to describe the disease characteristics, clinical practices, and survival related to PTLD in adult orthotopic liver transplant (OLT) recipients in South America. We conducted a survey at four different transplant groups from Argentina, Brazil, and Chile. Among 1621 OLT recipients, 27 developed PTLD (1.7%); the mean age at diagnosis was 53.7 (±14) yr with a mean time of 39.7 (±35.2) months from OLT to PTLD diagnosis. Initial therapy included reduction in immunosuppression alone in 23.1% of the patients. Either rituximab or chemotherapy was employed as initial or second‐line therapy in 76.9% of the patients. PTLD location was frequently extranodal (80.7%) and mostly involving the transplanted liver (59.3%). The overall survival at one and five yr post‐PTLD diagnosis was 53.8% and 46.2%, respectively. Significant univariate risk factors for post‐PTLD mortality included lactate dehydrogenase ≥250 U/L (HR 9.66, p = 0.02), stage III/IV PTLD (HR 5.34, p = 0.004), and HCV infection (HR 7.68, p = 0.01). In conclusion, PTLD in OLT adult recipients is predominantly extranodal, and although mortality is high, long‐term survival is possible.